2022
DOI: 10.3389/fmars.2022.1115275
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Live feed for early ontogenetic development in marine fish larvae

Abstract: Editorial on the Research Topic:Live feed for early ontogenetic development in marine fish larvae 1 PrefaceLive feeds hold the key to a stable and expanding marine aquaculture. In this editorial, we briefly review the history of live feed production for marine larviculture and summarize the latest contribution issued in the research topic -Live Feed for Early Ontogenetic Development in Marine Fish Larvae. With the current research that were submitted to this research topic, we see trends into many different as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
1
0
Order By: Relevance
“…Copepod biomass production has become one of the major interests in aquaculture for the last two decades (Doan et al, 2018; Drillet et al, 2006, 2011; Grønning et al, 2019; Nguyen et al, 2020) due to the high nutritional value, size variations, and behavior of copepods which may be relevant for larvae of many aquaculture species (Drillet et al, 2006, 2011; Pan, Dahms, et al, 2022; Pan, Souissi, & Jepsen, 2022). Calanoid copepod species have high levels of highly unsaturated fatty acids (HUFA) which are essential for the normal development of marine fish larvae and juveniles (Drillet et al, 2006, 2008; Pan, Dahms, et al, 2022; Pan, Souissi, & Jepsen, 2022; Rasdi & Qin, 2016; Rayner, Hwang, & Hansen, 2017). However, copepod density is typically lower than 400 adult individuals L −1 tropical and subtropical aquaculture ponds (Blanda et al, 2015; Grønning et al, 2019) which typically results in low production and is still a major limitation of copepod biomass production (Grønning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Copepod biomass production has become one of the major interests in aquaculture for the last two decades (Doan et al, 2018; Drillet et al, 2006, 2011; Grønning et al, 2019; Nguyen et al, 2020) due to the high nutritional value, size variations, and behavior of copepods which may be relevant for larvae of many aquaculture species (Drillet et al, 2006, 2011; Pan, Dahms, et al, 2022; Pan, Souissi, & Jepsen, 2022). Calanoid copepod species have high levels of highly unsaturated fatty acids (HUFA) which are essential for the normal development of marine fish larvae and juveniles (Drillet et al, 2006, 2008; Pan, Dahms, et al, 2022; Pan, Souissi, & Jepsen, 2022; Rasdi & Qin, 2016; Rayner, Hwang, & Hansen, 2017). However, copepod density is typically lower than 400 adult individuals L −1 tropical and subtropical aquaculture ponds (Blanda et al, 2015; Grønning et al, 2019) which typically results in low production and is still a major limitation of copepod biomass production (Grønning et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that biological factors 45 such as plankton availability are important for the natural diet of lobster larvae (O'Rorke et al 2014), and marine plankton are important for most marine species including molluscs and fishes (Pan, Souissi, and Jepsen 2022). For instance, the plankton Oithona sp., which has 50 been previously reported to be abundant 30 areas of lobster larvae (Amin et al 2022a;Boudreau, Simard, and Bourget 1992;Lillis and Snelgrove 2010).…”
Section: Introductionmentioning
confidence: 99%